Application of gravity method in cultural harritage Cot Sidi Abdullah Site, Samudera Pasai, North Aceh - NOVIA PURNAMA SARI; TOMI AFRIZAL; FAISAL ABDULLAH; NAZLI ISMAIL (Universitas Syiah Kuala, 2020)
The gravity method was applied to the cultural heritage site of Cot Sidi Abdullah in Kuta Krueng Village, Samudera Pasai District, North Aceh Regency for mapping and reconstruction structure of the cultural heritage site and distribution of artifact objects buried in the subsurface. Data measurement was carried out in a grid with 2 meters spacing between the points to cover all area of the cultural heritage site. The model of gravity anomaly distribution from the vertical derivative results shows a square pattern of anomaly gravity surrounding the measurement areas. This anomaly pattern is thought as a response from the remaining walls of the site structure which are buried in the subsurface with anomalous values between 0.02 mGal/m - 0.08 mGal/m. The estimation of the walls of the archaeological site from the anomalous response to this gravity value is proved by the excavation results in the southern part of the study area. While the minimum value of the vertical derivative filter (-0.06 mGal/m to - 0.01 mGal/m) is the response from the area around the archaeological site. The reconstruction results of the site based on the estimation of the walls with a length of ± 45 meters and a width of ± 40 meters.